Alternative solution for the dynamic equation of the bosonic string - Huamani, Richard (2022)
In this article, initially, a review of some classical aspects of bosonic string theory is made. In addition, the light cone coordinates are analyzed, as a covariant quantization method related to these coordinates with the proper coordinates through an appropriate transformation. This work aims to show an alternative way to deduce the solutions of string dynamic equation. For that, it starts transforming the light-cone coordinates by means of an arbitrary variable parameter, and by applying it into the Polyakov's action leads to equivalent solutions to the ones obtained using Fourier's series method.